DESIGN AND DEVELOP A GROUND MOVEMENT MONITORING SYSTEM AND A RAINFALL SIMULATOR ON THE LABORATORY SCALE LANDSLIDE SIMULATOR - AMRI (NIM : 20215004), IFUL
The continuous measurement of ground movement was implemented in order to understand more about relationship between trigger factor and dynamics of ground movement. Therefore, research of early warning system for landslides has been developed extensively. One of the systems used to monitor landslide disaster mitigation is an extensometer. Therefore, different types of extensometers have been developed by researchers, such as wire extensometer, borehole extensometer, extensometer based fiber optic, manual extensometer and digital extensometer. However, there are a lot of room for the improvement of the existing systems. The shortcomings include the large dimension, the low stability, and the high power consumption of the sensors. Therefore, the goal of this study was to develop a digital magnetic extensometer system with low-power consumption. The working principle was based on rotary encoder so the power consumption can be reduced. The module mainly composed of a spring balancer, a pulley, a rotary encoder, and a reed switch. The spring balancer was used to turn the pulley back to its initial point, the pulley was used as the medium between system and ground, and the rotary encoder which consists of a system of discs with magnet configuration on its side and the reed switches, was used to detect the movement by applying switching process caused by rotation of magnet. All the process in the system would be controlled by a microcontroller Atmega328p. Moreover in this digital extensometer, we implemented three discs with various diameters and magnet configuration so that varying levels of resolution at 1 mm, 1.5 mm, and 2 mm were generated. To reduce error, a bouncing circuit was installed. The extensometer was tested on a laboratory scale landslide simulator equipped with a rainfall simulator. This extensometer is proven to be able to generate stable, precise and accurate data. Hence, the extensometer is a reliable module required to monitor a rainfall-induced shallow landslides on a slope.